2020
DOI: 10.1016/j.jcct.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Standardized reporting systems for computed tomography coronary angiography and calcium scoring: A real-world validation of CAD-RADS and CAC-DRS in patients with stable chest pain

Abstract: A B S T R A C TObjectives: To assess the prognostic implications of standardized reporting systems for coronary computed tomography angiography (CCTA) and coronary artery calcium scores (CACS) in patients with stable chest pain. Background: The Coronary Artery Disease Reporting And Data System (CAD-RADS) and Coronary Artery Calcium -Data and Reporting System (CAC-DRS) aim to improve communication of CACS and CCTA results, but its influence on prognostication is unknown. Methods: Images from 1769 patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…These patients had 3 vessel disease ≥ 70% or left main stem stenosis ≥ 50%. This finding was in keeping with other researches which have reported that the presence of obstructive CAD is associated with a poorer prognosis [ 16 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These patients had 3 vessel disease ≥ 70% or left main stem stenosis ≥ 50%. This finding was in keeping with other researches which have reported that the presence of obstructive CAD is associated with a poorer prognosis [ 16 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…These patients had 3 vessel disease ≥ 70% or left main stem stenosis ≥ 50%. This finding was in keeping with other researches which have reported that the presence of obstructive CAD is associated with a poorer prognosis [16][17][18][19]. The Duke Prognostic CAD Index was originally derived for important prognostic aspects with a more detailed information of coronary anatomy than the traditional CAD classification of normal, one, two and three-vessel disease, and has been widely used to assess the mortality risk for treatment modalities based on the severity of coronary disease severity [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…Lastly, there is increasing demand for standardised reporting of CTCA findings. The CAD-RADS or ESCR smart reporting tool are standardised communication and reporting methods that link CTCA findings to further management recommendations and provide additional prognostic information of future CAD events [ 11 , 23 , 24 ]. Although the majority of hospital organisations (76.2%) use a standard report, only a minority (14.3%) used the CAD-RADS reporting system.…”
Section: Discussionmentioning
confidence: 99%
“…CAD-RADS is a standardised radiological reporting system dating since 2016, and there are only a few studies published in the area of cardiac imaging using the CAD-RADS score 28–32. It is used to quantify coronary artery stenosis in patients with suspected or known coronary artery disease to provide a basis for further investigation, diagnosis, management and treatment, substantially reducing human error and improving data integrity 14…”
Section: Discussionmentioning
confidence: 99%